STRATEGI KREATIF SIGN SYSTEM UNIVERSITAS SAHID SURAKARTA - Evelyne Henny Lukitasari (Akademi Seni dan Desain Indonesia Surakarta, 2021)
Creative strategies are designed by exploring problems in the surrounding environment and compiling creative ideas that are able to create designs that are useful for the community and the environment. Sign system in the context of visual communication design is a series of visual representations that have a purpose as a medium for human interaction in a public space that functions as information and a pointer from a location or place even from an appeal. This is done so that a communication process can be understood and agreed upon by many people on an ongoing basis. The sign system in this case is a wayfinding which is also formed from a pictogram. The pictograms are then used as a means of communicating through visual language. Pictograms through visual language make people see as well as read and analyze the meaning of the displayed image which sees, reads and analyzes pictograms which will develop problem solving habits, sensitivity and discipline awareness.This research is a qualitative study using a descriptive method with a semiotic approach. Methods of data collection using literature study, observation, and interviews. To develop a pictogram it was used to analyze and design wayfinding at Sahid University Surakarta.